Thermal and rheological characterization of bitumen modified with microencapsulated phase change materials. (10th August 2019) - Kakar, Muhammad Rafiq; Refaa, Zakariaa; Worlitschek, Jörg; Stamatiou, Anastasia; Partl, Manfred N.; Bueno, Moises
Graphical abstract: Highlights: Incorporation of microencapsulated phase change materials in asphalt binders provides thermal energy storage in latent form. PCM encapsulation is very important to avoid its direct interaction with bitumen. Replacing filler with equivalent volume of μPCM (3% by mass of bitumen) does not alter the bitumen rheological performance. The possibility of μPCM survival differs depending on the bitumen hardness. Abstract: The growing interest in the application of phase change materials (PCMs) and their benefit of storing or releasing thermal energy, attracted material scientists to investigate the suitability of PCM in bituminous road paving materials and to study the rheology of PCM-modified bitumen in particular. The use of PCM in road paving materials can contribute to minimize the distresses from seasonal extreme temperature variations in asphalt mixtures. In order to avoid or delay freezing and extreme low temperatures in asphalt pavements, the application of low temperature PCMs can be of great importance. Therefore, bitumens (160/220, 70/100 and 10/20) modified with microencapsulated PCM (µPCM) at low melting temperature were investigated. The dynamic shear rheometer (DSR) and differential scanning calorimetry (DSC) were used to evaluate the mechanical and thermal properties respectively. Based on the results, modification with 3% µPCM by mass of bitumen has no adverse effects on bitumen rheology but the advantage of minimizing/regulating temperature variations. Furthermore, it is anticipated that the protection of phase change materials as in this case using a polymeric shell is very important for its use in bitumen without reducing its rheological performance.